Intergenerational Biographical Structuring - Wolfram Fischer (Forum: Qualitative Social Research, 2008)
Presupposing the thesis of interactive biographical structuring, two narrative-biographical interviews of a mother and her son are analyzed by looking at the process of biographical co-construction. The inter-generational case reconstruction reveals how the process of biographical co-structuring results in a long-lasting highly problematic life situation of the son. At the time of the interview he permanently lives in a youth welfare institution, after expulsion from school at age ten as well as being committed to a psychiatric clinic for children and youth. Perspectives for social work and therapeutic intervention will be drawn from this analysis. URN: urn:nbn:de:0114-fqs0801493